2011
DOI: 10.3354/meps09315
|View full text |Cite
|
Sign up to set email alerts
|

Symbiodinium diversity in mesophotic coral communities on the Great Barrier Reef: a first assessment

Abstract: Despite a growing interest in mesophotic coral ecosystems (MCEs), information on the photosynthetic endosymbionts (genus Symbiodinium) associated with scleractinian corals inhabiting deep reef ecosystems is sparse. Here, the deep-water Symbiodinium diversity is assessed from 10 different coral genera at a depth range of 45 to 70 m on the Great Barrier Reef (GBR), Australia. Symbiodinium identity was established using denaturing gradient gel electrophoresis (DGGE) fingerprinting of the internal transcribed spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 56 publications
3
35
1
Order By: Relevance
“…Coral-Symbiodinium association on the upward-facing surface of the colonies followed a host-specific rather than a depth-specific pattern supporting data from the Great Barrier Reef (Bongaerts et al, 2011) and the Caribbean (Bongaerts et al, 2013). Although one species of Leptoseris hosted clade D symbionts in shallow water and other corals of this genus were associated with clade C symbionts in deep water, there was no symbiont species overlap between depths, and hence we could not identify depthdependent shifts of the main Symbiodinium types as reported for other coral species (Frade et al, 2008b;Lesser et al, 2010;Cooper et al, 2011).…”
Section: Coral-symbiodinium Depth Structure and Partitioningsupporting
confidence: 61%
“…Coral-Symbiodinium association on the upward-facing surface of the colonies followed a host-specific rather than a depth-specific pattern supporting data from the Great Barrier Reef (Bongaerts et al, 2011) and the Caribbean (Bongaerts et al, 2013). Although one species of Leptoseris hosted clade D symbionts in shallow water and other corals of this genus were associated with clade C symbionts in deep water, there was no symbiont species overlap between depths, and hence we could not identify depthdependent shifts of the main Symbiodinium types as reported for other coral species (Frade et al, 2008b;Lesser et al, 2010;Cooper et al, 2011).…”
Section: Coral-symbiodinium Depth Structure and Partitioningsupporting
confidence: 61%
“…Kahng et al [2] reported 26 papers from 16 regions in their 2010 review of MCEs for zooxanthellate corals, as well as papers on fish and algae. Additional data are now available from: the Red Sea [12,13], the Caribbean [14,15], the central Pacific [16][17][18], the Great Barrier Reef [19,20], and others. However, the techniques employed, the questions asked and the taxa considered are variable.…”
Section: Open Accessmentioning
confidence: 99%
“…The genus Symbiodinium can be categorised into eight distinct phylogenetic clades (A-H) based on their ribosomal DNA sequence (ITS2), with five of these (A-D and F) found in association with the corals (Baker, 2003). A high degree of host specificity (LaJeunesse et al, 2004(LaJeunesse et al, , 2010, habitat partitioning and ecological diversification have been identified as controlling factors of the distribution of the different Symbiodinium clades (Douglas, 1998;LaJeunesse et al, 2003;LaJeunesse, 2005;Stat et al, 2008a;Bongaerts et al, 2010Bongaerts et al, , 2011bLaJeunesse et al, 2010;Silverstein et al, 2011). To date the main role of Symbiodinium in the coral holobiont is thought to be through its involvement in its host's metabolism, including photosynthesis and nutrient cycling, which provides their hosts with up to 95% of their carbon requirements (Muscatine and Porter, 1977) and the cycling of nitrogenous compounds (Leggat et al, 2007;Pernice et al, 2012).…”
Section: Introductionmentioning
confidence: 99%